The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/sia.5096
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the addition of talc on tribological properties of aramid fiber‐reinforced polyimide composites under high vacuum, ultraviolet or atomic oxygen environment

Abstract: The aramid fibers-reinforced polyimide composites filled with talc were fabricated by means of a hot press molding technique, and mechanical and tribological behaviors were comparatively investigated. Experimental results showed that the elastic modulus of the composites increased with an increase of the talc, but the impact intensity and loss factor decreased. Besides, the coefficient of friction decreased with the increase of the talc content. To contrast the effects of the ultrahigh vacuum (VC), ultraviolet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
(21 reference statements)
1
13
0
Order By: Relevance
“…In addition, the polymer materials used on spacecraft surfaces are also vulnerable to UV and electron radiations. The UV radiation in the LEO (from 100 to 400 nm) has a strong destructive effect on the polymer material, which can result in the photodegradation of the molecular chains, changes in the surface morphology, and the deterioration of the mechanical properties . Meanwhile, EI induces changes in the surface morphology and chemical structure that arise from the breaking and degradation of the polymer chains .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the polymer materials used on spacecraft surfaces are also vulnerable to UV and electron radiations. The UV radiation in the LEO (from 100 to 400 nm) has a strong destructive effect on the polymer material, which can result in the photodegradation of the molecular chains, changes in the surface morphology, and the deterioration of the mechanical properties . Meanwhile, EI induces changes in the surface morphology and chemical structure that arise from the breaking and degradation of the polymer chains .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber-reinforced polymer composites have inherent advantages which highlight the high modulus, low coefficient of friction and good wear resistance [13][14][15][16][17]. Moreover, aramid fibers have also been proven to be an effective reinforcing agent due to high tensile strength/modulus and good thermal resistance [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the elastic modulus of the composites increased with an increase of the talc, but the impact intensity and loss factor decreased. Besides, the coefficient of friction decreased with the increase of the talc content [9]. Song provided some useful information on the tribological performance of thermoplastic polyimide (TPI) reinforced with rigid glass fillers of different shapes and sizes under dry, water, and oil lubrication conditions and found that fiber-reinforced TPI has favorable wear-resistance due to its shape [10].…”
Section: Introductionmentioning
confidence: 99%